Analisis Kelayakan Usaha Peternak Ayam Petelur - Nur Jannah; Sitti Hajerah Hasyim; Anisa Nurulita Hasani (Jurnal Ecogen, 2022)
This study objective to analyze the feasibility of laying hens "Clever Chicken" located in Tanete Riattang District, Bone Regency. The method used is qualitative and quantitative methods known as mixed methods. Data collection techniques through interviews, observations and literature. The results showed that (1) based on the legal aspects of the laying hens business "Clever Chicken" had fulfilled the business license and obtained permission from the surrounding community so that it was feasible to run, (2) based on the market aspect seeing market conditions with increasing demand and the existence of strategy in selling eggs so that this business is feasible to run, (3) based on the financial aspect, which consist of NPV, IRR, Net B/C, Gross B/C, BEP and PBP analysis, the laying hens business "Clever Chicken" in Tanete Riattang District, Bone Regency is feasible to run.